SILENT CRISIS: THE LACK OF INTEREST IN TEACHING DEGREES THREATENS THE FUTURE OF EDUCATION (Editora Impacto Científico, 2025)
This study analyzes government policies and institutional initiatives to attract and retain talent in the teaching profession. Through a literature review of 30 academic articles, we identified teacher training policies, financial incentives, and institutional programs aimed at valuing educators. We observed that while these policies and initiatives have the potential to promote education quality, they face challenges such as lack of financial resources and administrative bureaucracy. However, continuous training programs, emotional support, and improvement of working conditions have shown a positive impact on teacher satisfaction and retention in the profession. We conclude that urgent collective action is needed to reverse the declining trend in the demand for teaching courses and ensure a solid educational future.